2010
DOI: 10.1002/chem.201000120
|View full text |Cite
|
Sign up to set email alerts
|

Smart Trypsin Adsorption into N‐(2‐Aminoethyl)‐3‐aminopropyl‐Modified Mesoporous Silica for Ultra Fast Protein Digestion

Abstract: Comprehension of protein networks and expression patterns in cells, tissues, and organisms is essential for technological applications of modern life sciences. Due to the recent developments over the past few years, mass-spectrometry-based proteomics has expanded its interface role to broad and diverse research areas of science and technology. [1][2][3] Even so, to satisfy the demand for high-speed analysis, new flexible and efficient tools are an urgent priority.Peptide mass fingerprinting remains the most po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 25 publications
(28 reference statements)
1
19
0
Order By: Relevance
“…Following by pH change and applying trypsin, the denaturation and concurrent proteolysis of broad-range proteins could be efficiently achieved, resulting in the identifications of a broad range of diverse proteins with high sequence coverage by mass spectrometry. Similarly, trypsin immobilization on SBA-15 or amine and cyano functionalized SBA-15 materials have also been applied for protein proteolysis [54][55][56]. Casadonte et al [54] found that the amine functionalized SBA-15 showed higher digestion efficiency than unmodified SBA-15 with the same pore diameters.…”
Section: Enzymatic Reactor For Protein Digestionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following by pH change and applying trypsin, the denaturation and concurrent proteolysis of broad-range proteins could be efficiently achieved, resulting in the identifications of a broad range of diverse proteins with high sequence coverage by mass spectrometry. Similarly, trypsin immobilization on SBA-15 or amine and cyano functionalized SBA-15 materials have also been applied for protein proteolysis [54][55][56]. Casadonte et al [54] found that the amine functionalized SBA-15 showed higher digestion efficiency than unmodified SBA-15 with the same pore diameters.…”
Section: Enzymatic Reactor For Protein Digestionmentioning
confidence: 99%
“…Similarly, trypsin immobilization on SBA-15 or amine and cyano functionalized SBA-15 materials have also been applied for protein proteolysis [54][55][56]. Casadonte et al [54] found that the amine functionalized SBA-15 showed higher digestion efficiency than unmodified SBA-15 with the same pore diameters. Also, the proteolytic efficiency of functionalized SBA-15 was 1000 times faster than that of using conventional free solution method.…”
Section: Enzymatic Reactor For Protein Digestionmentioning
confidence: 99%
“…More importantly, some IMERs could be readily coupled to separation and identification systems, enabling fast, efficient, high-throughput and automated proteome analysis [7]. Till now, enzymes have been immobilized on different supports, such as membranes [8], carbon materials [9], monolithic materials [10][11][12][13][14][15][16][17], polymers [18][19][20][21], silica materials [22,23] and hybrids [24]. However, the improved binding capacity of enzymes and the decreased peptide residue on matrices are still the hot-points under serious consideration in this field.…”
Section: Introductionmentioning
confidence: 99%
“…The use of aminated organosilicas to adsorb acidic enzymes was recently reported (Casadonte et al, 2010). In this contribution, a simple protocol based on the use of carbodiimides to couple amino groups with the free carboxyl groups of the enzymes enables fast and efficient covalent binding on the NUVM-7 supports.…”
Section: Discussionmentioning
confidence: 99%
“…In these supports, immobilisation is usually carried out by adsorption based on electrostatic affinity between the amino groups of the enzyme and the hydroxyl groups of the support. The support can be functionalised with amino groups or activated with glutaraldehyde to link them to carboxyl groups of the enzyme (Subramanian et al, 1999;Casadonte et al, 2010).…”
Section: Introductionmentioning
confidence: 99%